KETERWAKILAN PEREMPUAN DI DPRD KABUPATEN ROKAN HULU PERIODE 2019-2024 - Dicky Rifaldo; Ali Yusri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2023)
The 1945 Constitution of the Republic of Indonesia emphasizes that the position of men and women as citizens is equal. A minimum quota of 30% for women's representation is implemented in the law on political parties. The level of representation of women in Indonesian politics is something that needs to be considered in democratic participation, one of which is the capital they have. This study explains the capital owned by female candidates in the General Election (Pemilu) with an analysis focus on the Rokan Hulu Regency DPRD in 2019. This study aims to determine the representation of women in the Rokan Hulu Regency DPRD for the 2019-2024 period. This study uses the study of Milbraith's theory which consists of factors of social capital, economic capital and cultural capital. The method in this study uses a descriptive research type using a qualitative approach. Sources of data consist of primary data and secondary data collected through interviews and documentation. Data analysis used qualitative data analysis techniques. The results of this study indicate that in the election for the 2019-2024 period, women's representation in the Rokan Hulu Regency DPRD from only 2 women legislative members as women's representation in members of the Rokan Hulu Regency DPRD is still very low. The results of the study suggest that women's representation should be increased with female candidates better preparing themselves starting from social capital. Economic capital and cultural capital. Keywords: Decrease, Representative Number, Women